Teori Belajar Sosial Sebagai Kerangka Analisis Motif Penggunaan Narkotika - Ciek Julyati Hisyam; Aisyah Aisyah; Defano Tanur; Diah Lestari; Marsya Nisa Razita; Nadia Dwi Nur Aufa (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
This research is motivated by the many deviant phenomena in narcotics use that occur in Indonesia today. This research aims to determine the process of social interaction in individuals which can influence them to take action. Similar to Sutherland's social learning theory, this research wants to find out what areas can influence the use of narcotics by individuals in their social interactions. The research process used descriptive methods and a qualitative approach through in-depth direct interviews with informants. In the process of interviews with informants, we found that the informant's narcotics abuse was the result of the influence of long-standing social interactions.